2015
DOI: 10.4103/0975-5950.168238
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of topical application of turmeric gel and 0.2% chlorhexidine gluconate gel in prevention of gingivitis

Abstract: Introduction:Turmeric commonly known as “Haldi” is a popular spice frequently used in Indian foods and curry. Turmeric holds a high place in Ayurvedic medicine as a “detoxifier of the body,” and today, science has documented several diseased conditions that can be healed by the active ingredients of turmeric. Curcumin is the most active constituent of turmeric curcuminoids obtained from the rhizome of Curcuma longa. Curcumin has been found to have antioxidant, anti-tumor, anti-inflammatory, antiviral, antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…The mean PI, GI and PPD in both the groups decrease after the treatment, and the decrease was more evident in Group II (Vajradanti) than Group I. Similar studies have been done previously with herbs like turmeric where the authors have evaluated the effect of turmeric on clinical parameters using the PI, GI, and PPD and found that turmeric gel can be effectively used as an adjunct to mechanical plaque control in the prevention of plaque and gingivitis [7].…”
Section: Discussionsupporting
confidence: 61%
“…The mean PI, GI and PPD in both the groups decrease after the treatment, and the decrease was more evident in Group II (Vajradanti) than Group I. Similar studies have been done previously with herbs like turmeric where the authors have evaluated the effect of turmeric on clinical parameters using the PI, GI, and PPD and found that turmeric gel can be effectively used as an adjunct to mechanical plaque control in the prevention of plaque and gingivitis [7].…”
Section: Discussionsupporting
confidence: 61%
“…However, our results differ from Singh et al . 2015,[ 23 ] wherein reduction in PI at end of 2 nd and 3 rd week was better in CHX group. Similarly, the decrease of mean GI was evidently higher in Group CHX than Group CMN.…”
Section: Discussionmentioning
confidence: 99%
“…It is even being pursued as a preventative measure and as a treatment for Alzheimer's disease (Mishra and Palanivelu, ; Mori, ). Turmeric oil has been tested against ocular and gingival infection models (Singh et al ., ; Singh et al ., ), with modestly successful results in comparison with contemporary antibiotic therapies. Turmeric and curcumin's efficacy against various infectious organisms likely results from multiple mechanisms; theories include curcumin's ability to perturb bacterial membranes, inhibit replication machinery, change gene expression, and even impair biofilm formation.…”
Section: Introductionmentioning
confidence: 99%